Management of Western Corn Rootworm (Diabrotica virgifera virgifera) - Sivčev, Ivan Lazar; Kljajić, Petar; Kostić, Miroslav; Sivčev, Lazar; Stanković, Sladjan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Western Corn Rootworm (WCR) was registered for the first time in Europe in 1992 in Serbia, near the international airport Surčin. spread of WCR on the territory of Serbia, as well as population density increase, was fast (Sivčev et al., 1994; Sivčev and Tomašev, 2002). Territory of Serbia was entirely populated in the following few years, while major damages on corn occurred on corn grown for two of more years on the same field. Data regarding damages on over 140,000 ha under corn until 1999 were collected by organized monitoring. After 2000 and 2003, population abundance of D. v. virgifera as well as the number of damaged corn fields, significantly decreased due to drought and application of crop rotation. Corn rootworm has one generation per year. It overwinters in egg stadium. Under climatic conditions of Serbia larvae hatching starts around May 15th. The highest number of larvae on root is observed around June 20th when feeding is the most intensive and plant lodging occurs as they lose their roots. First adults emerge by the end of June. Their abundance increases during July and reaches maximum by the end of the month. From the second decade of August the abundance decreases. Adults are present in the field until the first frosts occur. larvae are much more harmful and significant than adults. Larvae feed on root or in root by boring. Root can be entirely destroyed in the case of heavy attack and these plants lodge already at the end of June. Under our climatic and agrotechnical conditions, adults are sporadic pests. Adults are a threat only in cases of sowing after optimal sowing date or in case of stubble corn sowing Crop rotation is efficient and most widespread means of WCR control. No damage on corn grown in crop rotation has been registered in Serbia for now. In the first year of production corn does not require protection from Diabrotica virgifera virgifera LeConte larvae. Several insecticides performed high efficacy by application at sowing time and are registered for commercial use. However, application of soil insecticides on larger areas was never done in Serbia.
Keywords: Pest management; Maize; Insecticides; Western Corn Rootworm